2015
DOI: 10.1002/mc.22406
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy levels are elevated in barrett's esophagus and promote cell survival from acid and oxidative stress

Abstract: Autophagy is a highly conserved mechanism that is activated during cellular stress. We hypothesized that autophagy may be induced by acid reflux, which causes injury and inflammation, and therefore contributes to the pathogenesis of Barrett’s esophagus (BE) and esophageal adenocarcinoma (EAC). Currently, the role of autophagy in BE and EAC is poorly studied. We quantitatively define autophagy levels in human BE cell lines, a transgenic mouse model of BE, and human BE and EAC biopsies. Human non-dysplastic BE h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…It has been described earlier that dysplastic Barrett's mucosa has more severe and prolonged acidic and biliary reflux exposure (41). Furthermore, it has also been observed that CP-D cells are more resistant to GERD-like stimuli compared with CP-A cells (28). The mechanism for this alteration and its potential physiological role cannot be explained by the present studies and are areas of focus for future work.…”
Section: Discussionmentioning
confidence: 54%
“…It has been described earlier that dysplastic Barrett's mucosa has more severe and prolonged acidic and biliary reflux exposure (41). Furthermore, it has also been observed that CP-D cells are more resistant to GERD-like stimuli compared with CP-A cells (28). The mechanism for this alteration and its potential physiological role cannot be explained by the present studies and are areas of focus for future work.…”
Section: Discussionmentioning
confidence: 54%
“…41 PPI usage prior to endoscopy in 65 of the 67 human subjects in the current study precludes evaluation of the influence of refluxassociated inflammation upon autophagy; however, we find that autophagy facilitates survival in the context of acid stress in EPC2-hTERT cells and Barrett's oesophagus (BE)-derived cell lines. 42 Moreover, AV content is increased in oesophagi of mice with IL-1β-mediated inflammation prior to the onset of columnar metaplasia as well as in oesophageal biopsies from BE patients. 42 43 Thus, it is plausible that keratinocyte autophagy is activated in response to a diverse spectrum of stress signals, potentially contributing to the pathogenesis of multiple oesophageal disorders.…”
Section: Discussionmentioning
confidence: 98%
“…While Beclin‐1 expression and autophagy could be induced in these BE cell lines by acute exposure to deoxycholic acid, levels of this moiety decreased after chronic exposure. In contrast, other investigators, analyzing morphologic features of autophagic vesicles in biopsy specimens, showed that autophagy levels are increased in BE compared with normal squamous mucosa, though they are generally diminished relative to normal cells in dysplastic BE . Separate studies have demonstrated that the esophageal microbiome is altered in BE and esophageal adenocarcinoma.…”
Section: What Is the Role Of Autophagy In Gastroesophageal Reflux Dismentioning
confidence: 95%
“…In contrast, other investigators, analyzing morphologic features of autophagic vesicles in biopsy specimens, showed that autophagy levels are increased in BE compared with normal squamous mucosa, though they are generally diminished relative to normal cells in dysplastic BE. 53 Separate studies have demonstrated that the esophageal microbiome is altered in BE and esophageal adenocarcinoma. Interactions of this microbiome with autophagy have yet to be discovered.…”
Section: Autophagy In Inflammatory Disordersmentioning
confidence: 99%